2006
DOI: 10.1002/hep.20983
|View full text |Cite
|
Sign up to set email alerts
|

Insulin resistance is associated with steatosis in nondiabetic patients with genotype 1 chronic hepatitis C†

Abstract: Conflicting data exist regarding the relationship between hepatitis C virus genotype 1 and hepatic steatosis as well as the latter's role in the progression of fibrosis and treatment response. We assessed factors associated with hepatic steatosis in genotype 1 chronic hepatitis C and the impact of hepatic fat on fibrosis development and interferon responsiveness. Two hundred ninety-one non-diabetic patients with genotype 1 chronic hepatitis C were examined for the presence of steatosis and its correlation with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
108
0
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 151 publications
(126 citation statements)
references
References 43 publications
17
108
0
1
Order By: Relevance
“…Other mechanisms involving Tumour Necrosis Factor-a (TNF-a), development of hepatic steatosis and iron overload causing insulin resistance, lack of phosphatidylinositol (PI)-3 kinase activation have also been reported [20][21][22]. However, our study did not look into the aspect of pathogenesis causing IGT/ DM in our patients.…”
Section: Discussionmentioning
confidence: 70%
“…Other mechanisms involving Tumour Necrosis Factor-a (TNF-a), development of hepatic steatosis and iron overload causing insulin resistance, lack of phosphatidylinositol (PI)-3 kinase activation have also been reported [20][21][22]. However, our study did not look into the aspect of pathogenesis causing IGT/ DM in our patients.…”
Section: Discussionmentioning
confidence: 70%
“…As well as predisposing to T2DM, the presence of IR in CHC predicts non-response to antiviral therapy [26] , both for genotype 1 [26,[34][35][36] and genotypes 2 and 3 infection [37] . Central obesity, which can be associated with IR, has also been shown to predict non-response [38] .…”
Section: Complications Of Hcv-induced Irmentioning
confidence: 99%
“…Further exploration is needed to clarify the complex context of MS with respect to different ethnicity. Furthermore, emerging lines of clinical data revealed that several metabolic disturbance; such as obesity, IR, and hepatic steatosis, are significant risk factors for decreased treatment response to pegylated IFN (PegIFN) and ribavirin combination therapy in CHC patients (Bressler et al, 2003;Camma et al, 2006;RomeroGomez et al, 2005;Watanabe et al, 2008). The association between HCV infection and MS could be validated by the sequential changes of MS characteristics upon treatment response to antiviral therapy.…”
Section: Metabolic Disordersmentioning
confidence: 99%